2012
DOI: 10.1212/wnl.0b013e3182749e67
|View full text |Cite
|
Sign up to set email alerts
|

Video game–based coordinative training improves ataxia in children with degenerative ataxia

Abstract: This study provides Class III evidence that directed training with Xbox Kinect video games can improve several signs of ataxia in adolescents with progressive ataxia as measured by SARA score, Dynamic Gait Index, and Activity-specific Balance Confidence Scale at 8 weeks of training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(162 citation statements)
references
References 10 publications
3
141
0
9
Order By: Relevance
“…Third, more research concerning the measurement and treatment of childhood ataxia is needed. There are few reports specific to children regarding the measurement 37 and treatment of ataxia (pharmacologic [38][39][40][41][42] and nonpharmacologic [43][44][45] ). This may reflect the fact that the overall prevalence and importance of childhood ataxia has likely been underestimated in the past, despite the fact that ataxia is associated with significant economic cost and decreased quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Third, more research concerning the measurement and treatment of childhood ataxia is needed. There are few reports specific to children regarding the measurement 37 and treatment of ataxia (pharmacologic [38][39][40][41][42] and nonpharmacologic [43][44][45] ). This may reflect the fact that the overall prevalence and importance of childhood ataxia has likely been underestimated in the past, despite the fact that ataxia is associated with significant economic cost and decreased quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Balance training is an important intervention for patients with cerebellar ataxia [50,52,53,117]. A previous RCT study revealed that balance training with placement on the torso with less than 1.5% of patient's body weight improves gait ability in patients with cerebellar ataxia with MS [10,54].…”
Section: Balance Trainingmentioning
confidence: 99%
“…Wifred Ilg et al (2012) (19) Huiqiong Deng et al (2013) (10) CDR Tom Schroeder, USPHS (2013) (11) Jorge L Jorge-rodriguez et al (2013) (13) Jennifer L. Keller et al (2014) (18) 1 Eligibility criteria were specified…”
Section: Data Evaluationmentioning
confidence: 99%
“…Subjects were randomly allocated to groups (in a crossover study, subjects were randomly allocated an order in which treatment s were received) 3,13,15,[17][18][19] , and four level IV studies -3 case series and 1 case series of cross over design [10][11][12]16 ( 13,18 , Scale for Assessment And Rating of Ataxia (SARA) 14,19 , 3-D Motion capture analysis 11,19 , Postural sways using force platforms 13 . Many authors have also used self perceived scores by the subjects to evaluate their perception of improvement following Physiotherapy interventions.…”
Section: Data Evaluationmentioning
confidence: 99%
See 1 more Smart Citation